Análisis del discurso de la publicidad televisiva transmitida por canales de televisión abierta en la ciudad de Quito, a partir de las características del estereotipo de feminidad usado durante los últimos tres años - Guaño Arias, Stephanie Marisol (2013)
This analysis, about the advertising discourse of, TV wants to understand the relationship between the economic system and the femininity`s stereotype that is used in the advertising, that has been transmitted over the past three year in Quito. This advertising continues using women in the role of a happy housewife in private places and with her family. The other hand, this advertising uses a new women`s image: the modern woman, in public places, she is professional and successful. It isn´t an innocent situation, because the publicity changes for showing a kind of society: the society that the publicity is promoting. Understanding that advertising is a common thing in the city, and, the advertising discourse has a regulatory function in a context. we can conclude that publicity helps reproduce the economic system and is helping to naturalize the women´s stereotypes that reduces and homogenizes the “to be woman” because these stereotypes are promoting the correct ways for being woman, which are physical, moral, sexual and ethnic characteristics, these characteristic are part of a fiction about the happiness and the success of a woman, but, this happiness and success are gotten for using or having a product or a trademark.